Empowering Goat Farming: Implementing Complete Silage Rations from Local Resources in Talawi Hilie Village - Lendrawati, Lendrawati; Afriani, Tinda; Ratni, Eli (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2023)
This article presents an innovative approach to addressing the challenges faced by goat farmers in Talawi Hilie Village, Sawahlunto City, West Sumatra Province, Indonesia. The study focuses on implementing complete silage rations utilizing local agricultural and industrial by-products to improve goat nutrition and feed availability. Through community engagement and training, farmers were empowered with knowledge and skills in utilizing readily available feed resources, including rice straw, sugarcane tops, corn straws, coffee husks, and rice bran, for silage production. The training sessions included practical demonstrations of forage processing and silage preparation techniques. Results indicate that implementing complete silage rations effectively addressed the feed scarcity issue and improved the feed quality provided to goats. Farmers demonstrated enthusiasm and willingness to adopt the technology, leading to increased self-sufficiency and welfare improvement in the community. The study underscores the importance of community empowerment and utilization of local resources for sustainable livestock production. Further research is recommended to explore the long-term impact of complete silage rations on goat performance and productivity